DIGITAL FINANCIAL ADOPTION STRATEGY MODERATED BY FINANCIAL LITERACY AT BPR SYARIAH IN EAST JAVA - Putri Septi Naulina Hasibuan; Aminullah Assagaf; Sri Handini (International Journal of Social Science, 2025)
The use of technology in the banking sector through Financial Technology (digital finance) is expected to provide convenience in services for the public. However, its implementation still faces challenges due to the low level of public understanding regarding digital finance and investment. This study aims to analyse the influence of risk, ease of use, usefulness, and benefits on attitudes toward the use and adoption of digital finance, with financial literacy as a moderating variable. This quantitative research involved 180 respondents who are customers of BPR Syariah, selected using purposive sampling and the Slovin formula. Data were collected through questionnaires and analysed using SEM-PLS. The results indicate that risk has a negative effect, while ease of use, usefulness, and benefits have positive effects on attitudes toward the use and adoption of digital finance. Nevertheless, attitudes toward the use of digital finance do not significantly affect adoption, and financial literacy is not proven to moderate the relationship. These findings highlight that ease of use, usefulness, and benefits are more dominant factors in encouraging the use of digital finance compared to financial literacy itself